2009
DOI: 10.1143/jjap.48.09kf03
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characteristics of (Ba0.94Gd0.06)(Ti0.97Mg0.03)O3in Cubic Structure Determined by High-Energy Synchrotron-Radiation Powder Diffraction

Abstract: Structural study by high-energy synchrotron-radiation powder diffraction has been performed for (Ba 0:94 Gd 0:06 )(Ti 0:97 Mg 0:03 )O 3 (BGTM) at 473 K to investigate the substitution effects of Gd and Mg on the cubic structure of BaTiO 3 . Our precise electron-density analysis using the maximum entropy method (MEM)/Rietveld method demonstrates that the bonding electron density between the Ti and O atoms in BGTM decreases with the substitution of Gd and Mg elements, which provides a significant contrast to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…21) In our previous charge density study, it was shown that the substitution of Mg ions for Ti ions reduced the covalency between the B site and O ions. 16) This result indicates that the repulsion force between the B site and O ions was increased by Mg substitution. Both decreasing the temperature and increasing the Gd content reduced the average distance between the Ti=Mg and O ions, and increased the repulsion force between the ions.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…21) In our previous charge density study, it was shown that the substitution of Mg ions for Ti ions reduced the covalency between the B site and O ions. 16) This result indicates that the repulsion force between the B site and O ions was increased by Mg substitution. Both decreasing the temperature and increasing the Gd content reduced the average distance between the Ti=Mg and O ions, and increased the repulsion force between the ions.…”
Section: Resultsmentioning
confidence: 90%
“…17,18) Our previous electron charge density analysis by high-energy synchrotron radiation X-ray powder diffraction and the maximum entropy method (MEM)= Rietveld method revealed that the lower T C = 293 K of (Ba 0.94 Gd 0.06 )(Ti 0.97 Mg 0.03 )O 3 than of pure BaTiO 3 was caused by the decrease in the electron density of covalent bonding between the Ti site and O ions caused by the substitution of the Mg ion possessing no d-electrons. 16) This result made a contrast with the fact that the small T C change 19) and no apparent change in Ti-O bonding nature were observed in the (Ba 1−x Ca x )TiO 3 system. 20) The careful crystal structure analysis of (Ba 1−x Gd x )(Ti 1−x=2 Mg x=2 )O 3 revealed that Gd ions occupied the six 〈100〉 off-centered positions in the cubic phase of (Ba 1−x Gd x )(Ti 1−x=2 Mg x=2 )O 3 (0 < x ≤ 0.3) and the single site shifted along the [001] direction in the tetragonal phase of (Ba 0.94 Gd 0.06 )(Ti 0.97 Mg 0.03 )O 3 .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recent developments of electron charge density analyses using a high-energy synchrotron radiation (SR) diffraction technique enabled us to visualize the direct evidence of the bonding electron hybridizations between the B-site atoms and the O atom in many perovskite-type oxides in both prototype cubic and low-temperature phases. [27][28][29][30][31] Perovskite-type solid solution systems often have different symmetries in the low-temperature phases depending on the compositions, even if the high-temperature phase has the same cubic symmetry. BCT retains a tetragonal symmetry at room temperature up to the solubility limit, but the order parameter should depend on the composition because the tetragonal-orthorhombic phase transition temperature steeply decreases with increasing the Ca composition.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the capacitance of MLCCs composed of BT ceramics also rapidly decreases above T c . A large number of studies of their properties have been carried out, [2][3][4][5][6][7][8] but the T c of BT ceramics has not been increased by compositional modifications except for limited elements, such as Pb. 9, 10) In recent years, we have fabricated Sn and Ca codoped BT ferroelectric ceramics and examined the thermal features of their dielectric properties.…”
Section: Introductionmentioning
confidence: 99%